Driver's Physiological Measures With In-vehicle Secondary Distraction: A Systematic Review - Nor Kamaliana Khamis; Muhammad Aizat Shamsudin; Nurainaa Kabilmiharbi; Nor Azila Noh (UKM Press, 2024)
Jurnal Kejuruteraan 35(1) 2023 (page 35-47)